Refugees and expellees in rural Saxony: life after 1945 = Uchodźcy i wypędzeni na terenach wiejskich Saksonii po roku 1945 - Friedreich, Sonke; Spieker, Ira (Zielona Góra: Lubuskie Towarzystwo Naukowe)
As a consequence of the Second World War unleashed by Germany, millions of people were forced to stream into the areas that subsequently became the two successor states of the German Reich. The acceptance and integration of the refugees and displaced persons presented the society and the political leadership of the GDR (German Democratic Republic) with an enormous challenge.
Keywords: migracja; napływ i wydalenie; pogranicze; społeczności wiejskie; transformacja spoleczna; transformacja polityczna; II (druga) wojna światowa; migration; flight and expulsion; borderland; rural societies; political transformation; social transformation; world war II